2021
DOI: 10.5530/pj.2021.13.203
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Activity of the Leaf Extract of Eurycoma Longifolia Jack. in Streptozotocin-Nicotinamide Induced Diabetic Model

Abstract: Background: One of the medication attempts in diabetes mellitus is by utilising plants that are potent as an antioxidant. Eurycoma longifolia Jack. known as "Longjack" in English, is a medicinal plant and reportedly effective as an antioxidant. Objectives: This study was aimed to examine the antidiabetic effectiveness of ethanol extract of longjack leaf in diabetes mellitus rats. Methods: This study used the total of 24 male white rats which were grouped into four. The normal and the negative control groups we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…According to a previous study, normal rat blood glucose levels ranged from 50 -135 mg/dl (Puspitasari & Syauqy, 2015). These groups showed that all animal models did not have diabetes without STZ-NA induction (Panjaitan & Astuti, 2021). On the fourth day, a second blood glucose level measurement was taken to determine the increase in blood glucose levels after being induced with STZ-NA with a dose of STZ 45 mg/kg berat badan and a dose of NA 110 mg/kg berat badan.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…According to a previous study, normal rat blood glucose levels ranged from 50 -135 mg/dl (Puspitasari & Syauqy, 2015). These groups showed that all animal models did not have diabetes without STZ-NA induction (Panjaitan & Astuti, 2021). On the fourth day, a second blood glucose level measurement was taken to determine the increase in blood glucose levels after being induced with STZ-NA with a dose of STZ 45 mg/kg berat badan and a dose of NA 110 mg/kg berat badan.…”
Section: Discussionmentioning
confidence: 80%
“…The Na-CMC 0.5% administration group showed an increase in blood glucose levels combined with the highest malondialdehyde levels of 9.66 nmol/mL. According to a previous study, Na-CMC does not have potential compounds that can lower blood glucose and MDA levels (Panjaitan & Astuti, 2021). The glibenclamide administration group showed a decrease in glucose and MDA levels by 3.02 nmol/ml.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation